The Importance of Adult Education in India and Its Present-Day Relevance: Exploring the Impact of Adult Education on India's Economy, Crime Rates, and Social Development (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Though the concept of Adult Education is not given much weightage, the impact of Adult Education in any nation cannot be denied. The role played by adult’s education cannot be said to be very straight and direct however, indirectly, it influences various different factors. The adult population in any nation cannot be denied, and having a condition where adults have the knowledge and skills to take upon any tasks will undoubtedly boost the economy in a longer run. And not just the economic part which is under the limelight, but it is also the crime factor which comes into play. When analytical research is given as to why a certain country records a higher crime rate, one important reason is the illiteracy of people which instigates crime. The paper thus wants to highlight primarily the importance of adult education and the factors which are directly affected positively. The author also takes us through its historical development and explains as to where and how the concept of adult education grew. As a concluding remark, the author also stressed on the importance of Social Education among adults which can even be called as the need of the hour.